Mycorrhizal Fungi Influence on Mature Tree Growth: Stronger in High‐Nitrogen Soils for an EMF‐Associated Tree and in Low‐Nitrogen Soils for Two AMF‐Associated Trees - Inés Ibáñez; Morgan R. McPherson; Rima A. Upchurch; Donald R. Zak (Plant-Environment Interactions)
ABSTRACT The plant–mycorrhizal fungi relationship can range from mutualistic to parasitic as a function of the fungal taxa involved, plant ontogeny, as well as the availability of resources. Despite the implications this relationship may have on forest carbon cycling and storage, we know little about how mature trees may be impacted by mycorrhizae and how this impact may vary across the landscape. We collected growth data of two arbuscular mycorrhizal fungi (AMF)‐associated tree species, Acer rubrum and A. saccharum, and one ectomycorrhizal fungi (EMF)‐associated tree species, Quercus rubra, to assess how the mycorrhizal fungi–plant association may vary along a gradient of nitrogen (N) availability. Individual assessments of fungal taxa relative abundances showed non‐linear associations with tree growth; positive associations for the two AMF‐associated trees were mostly under low N, whereas positive to neutral associations for the EMF‐associated tree mainly took place at high N. Only A. rubrum exhibited greater tree growth with its tree soil‐specific mycorrhizal community when compared with predictions under a random mycorrhizal soil community. Because mycorrhizal fungi are likely to mediate how plants respond to warming, increasing levels of N deposition and of atmospheric CO2, understanding these relationships is critical to accurately forecasting tree growth.